2021
DOI: 10.3389/fcell.2021.693694
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia Response Element-Directed Expression of aFGF in Neural Stem Cells Promotes the Recovery of Spinal Cord Injury and Attenuates SCI-Induced Apoptosis

Abstract: Reducing neuronal death after spinal cord injury (SCI) is considered to be an important strategy for the renovation of SCI. Studies have shown that, as an important regulator of the development and maintenance of neural structure, acidic fibroblast growth factor (aFGF) has the role of tissue protection and is considered to be an effective drug for the treatment of SCI. Neural stem cells (NSCs) are rendered with the remarkable characteristics to self-replace and differentiate into a variety of cells, so it is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…However, the toxic microenvironment of the injury is unfavorable for survival of transplanted cells [ 18 ]. Previous studies reported that endogenous NSCs were activated after SCI in the central canal of the spinal cord, whereby they took part in the regeneration of neural function [ 19 , 20 ]. Therefore, promoting the proliferation and differentiation of NSCs can be an effective strategy for treatment of nerve injuries [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the toxic microenvironment of the injury is unfavorable for survival of transplanted cells [ 18 ]. Previous studies reported that endogenous NSCs were activated after SCI in the central canal of the spinal cord, whereby they took part in the regeneration of neural function [ 19 , 20 ]. Therefore, promoting the proliferation and differentiation of NSCs can be an effective strategy for treatment of nerve injuries [ 21 ].…”
Section: Introductionmentioning
confidence: 99%